Patient Satisfaction as a Mediator of Service Quality, Hospital Image, and Loyalty Among Participants of Indonesia’s BPJS Kesehatan Program - Luh Putu Widiarti; I Wayan Widnyana; Ni Wayan Eka Mitariani; I Made Dauh Wijana (International Journal of Applied Business and International Management, 2025)
Maintaining patient loyalty is a key challenge in public healthcare services. This study aims to examine the mediating role of patient satisfaction in the relationship between service quality, hospital image, and the Social Security Agency for Health (BPJS Kesehatan) participants' loyalty at RSUD Mangusada Badung. A quantitative method was employed by distributing questionnaires to BPJS participants who had received services at the hospital. The data were analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software. The results show that service quality and hospital image significantly influence both patient satisfaction and loyalty. Patient satisfaction also partially mediates the relationship between service quality, hospital image, and loyalty. Numerically, service quality has a path coefficient of X, hospital image Y, and patient satisfaction Z toward loyalty, all with significant p-values (p 0.05). These findings imply that improving service quality and maintaining a strong hospital image can enhance patient satisfaction and foster long-term loyalty among BPJS participants. The study contributes to healthcare service management literature and offers practical insights for hospital administrators and BPJS policymakers in formulating strategies to strengthen patient retention and institutional trust.